Lands and peoples. The world in color. Volume 3 : eastern Europe, Soviet Union, Middle East - Merrick, Helen Hynson
Greece -- Athens -- Albania -- Yugoslavia -- Bulgaria -- Rumania -- The Soviet Union -- Soviet Republics in Asia -- Caucasus Republics -- Iran -- Iraq -- Baghdad -- Turkey -- Istanbul -- Syria -- Lebanon -- Israel -- Jordan -- Bedouins -- The arabian Peninsula